Physical Towel Exercise Degung Sunda (TEDS): Upaya Mencegah Frailty pada Lansia - Lisna Nuryanti; Nurti Yunika Kristina Gea; Rotua Suriany Simamora; Feri Setiadi; Lisna Agustina (Universitas Pahlawan Tuanku Tambusai, 2026)
Frailty is a common geriatric syndrome characterized by decreased physiological reserves and increased vulnerability to stressors, significantly impacting the quality of life among older adults. This study aims to evaluate the effectiveness of Physical Towel Exercise Degung Sunda (TEDS) in reducing frailty levels in the elderly. A quasi-experimental pretest-posttest design was employed involving 136 participants aged 60-70 years residing in the community. Data were analyzed using a paired t-test with a two-tailed p-value (0.05) to assess changes in frailty status before and after the intervention. Results indicated a significant reduction in frailty, with the majority of participants shifting from moderate to light frailty categories post-intervention (p < 0.001). Specifically, the mean frailty score decreased from 1.77 (pre-test) to 1.46 (post-test), demonstrating improved physical function, balance, and muscular strength. The findings suggest that TEDS is an effective, low-cost, and easily implementable exercise intervention for preventing and delaying the progression of frailty among the elderly. These outcomes highlight the importance of structured physical activity in promoting healthy aging and enhancing overall well-being in older populations.